Mission to people of other faiths in the Old Testament and Eldoret, Kenya: some reflections for engaging Muslims within their context - R. Omwenga (Acta Theologica)
The election of biblical Israel in the Old Testament through Abraham and the mandate to represent God to other nations compare to Kenyan contexts of mission to people of other faiths by virtue of strengths and weaknesses. With an aim of providing reflections for contemporary practice, this article goes beyond these strengths and weaknesses by providing suggestions for how mission can be effectively undertaken in Eldoret, Kenya. As a context where mission begins, the Old Testament’s experience of engagements to other nations compare closely to the Kenyan experience, yet both lack perfect examples. Idolatry, unbelief and unfaithfulness to God’s commandments are some of the factors leading to Israel’s and Eldoret’s failure to faithfully represent God. This article highlights and discusses these and proposes recommendations for a better paradigm applicable to any Christian church functioning in an Islamic context.